Low-Dose Decitabine-Based Chemoimmunotherapy for Patients with Refractory Advanced Solid Tumors: A Phase I/II Report - Hui Fan; Xuechun Lu; Xiaohui Wang; Yang Liu; Bo Guo; Yan Zhang; Wenying Zhang; Jing Nie; Kaichao Feng; Meixia Chen; Yajing Zhang; Yao Wang; et al. (Journal of Immunology Research)
Aberrant DNA methylation is one of the main drivers of tumor initiation and progression. The reversibility of methylation modulation makes it an attractive target for novel anticancer therapies. Clinical studies have demonstrated that high-dose decitabine, a hypomethylating agent, results in some clinical benefits in patients with refractory advanced tumors; however, they are extremely toxic. Low doses of decitabine minimize toxicity while potentially improving the targeted effects of DNA hypomethylation. Based on these mechanisms, low-dose decitabine combined with chemoimmunotherapy may be a new treatment option for patients with refractory advanced tumors. We proposed the regimen of low-dose decitabine-based chemoimmunotherapy for patients with refractory advanced solid tumors. A favorable adverse event profile was observed in our trial that was highlighted by the finding that most of these adverse events were grades 1-2. Besides, the activity of our cohort was optimistic and the clinical benefit rate was up to 60%, and the median PFS was prolonged compared with PFS to previous treatment. We also identified a significant correlation between the PFS to previous treatment and clinical response. The low-dose DAC decitabine-based chemoimmunotherapy might be a promising protocol for improving the specificity and efficiency of patients with refractory advanced solid tumors. This trial is registered in the ClinicalTrials.gov database (identifier NCT01799083).